Coordinated Adsorption and Catalytic Conversion of Polysulfides Enabled by Perovskite Bimetallic Hydroxide Nanocages for Lithium‐Sulfur Batteries. Issue 31 (23rd June 2021) - Wang, Xinliang; Han, Junwei; Luo, Chong; Zhang, Bin; Ma, Jiabin; Li, Zejian; He, Yan‐Bing; Yang, Quan‐Hong; Kang, Feiyu; Lv, Wei
Abstract: Catalysis is an effective remedy for the fast capacity decay of lithium‐sulfur batteries induced by the shuttling of lithium polysulfides (LiPSs), but too strong adsorption ability of many catalysts toward LiPSs increases the risk of catalyst passivation and restricts the diffusion of LiPSs for conversion. Herein, perovskite bimetallic hydroxide (CoSn(OH)6 ) nanocages are prepared, which are further wrapped by reduced graphene oxide (rGO) as the catalytic host for sulfur. Because of the coordinated valence state of Co and Sn and the intrinsic defect of the perovskite structure, such bimetallic hydroxide delivers moderate adsorption ability and enhanced catalytic activity toward LiPS conversion. Coupled with the hollow structure and the wrapped rGO as double physical barriers, the redox reaction kinetics, and sulfur utilization are effectively improved with such a host. The assembled battery delivers a good rate performance with a high capacity of 644 mAh g −1 at 2 C and long stability with a capacity decay of 0.068% per cycle over 600 cycles at 1 C. Even with a higher sulfur loading of 3.2 mg cm −2 and a low electrolyte/sulfur ratio of 5 µL mg −1, the battery still shows high sulfur utilization and good cycling stability. Abstract : Perovskite CoSn(OH)6 nanocages wrapped by reduced graphene oxide are used as catalytic sulfur hosts, which show moderate adsorption ability and enhanced catalytic activity due to the coordinated valence state of Co and Sn and the intrinsic defect of the perovskite structure. The assembled Li‐S battery shows good cycling stability due to the enhanced polysulfide conversion kinetics and sulfur utilization.